2001
DOI: 10.1094/mpmi.2001.14.5.653
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Subtilase from the Vascular Wilt Fungus Fusarium oxysporum

Abstract: The gene prt1 was isolated from the tomato vascular wilt fungus Fusarium oxysporum f. sp. lycopersici, whose predicted amino acid sequence shows significant homology with subtilisin-like fungal proteinases. Prt1 is a single-copy gene, and its structure is highly conserved among different formae speciales of F. oxysporum. Prt1 is expressed constitutively at low levels during growth on different carbon and nitrogen sources and strongly induced in medium containing collagen and glucose. As shown by reverse transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 42 publications
0
28
0
3
Order By: Relevance
“…For instance, decrease in pathogenicity of trypsin deficient mutants of C. carbonum graminoid pathogen with deficiency of trypsin like proteinases was not observed [16]. Directed inactivation of subtilisin like extracellular Prt1 proteinase of the fungus F. oxysporum did not affect its pathogenicity towards tomatoes [24]. These and other similar data [27,34] suggest that in certain cases the role of the extracellular proteinases is limited to providing phytopathogenic microorganisms with amino acids essential for their growth and development [35].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…For instance, decrease in pathogenicity of trypsin deficient mutants of C. carbonum graminoid pathogen with deficiency of trypsin like proteinases was not observed [16]. Directed inactivation of subtilisin like extracellular Prt1 proteinase of the fungus F. oxysporum did not affect its pathogenicity towards tomatoes [24]. These and other similar data [27,34] suggest that in certain cases the role of the extracellular proteinases is limited to providing phytopathogenic microorganisms with amino acids essential for their growth and development [35].…”
mentioning
confidence: 93%
“…The first group contains proteinases that are produced by Cochliobolus carbonum [16], Verticillium dahliae [17,18], Stagonospora (Septoria) nodorum [19], and Phytophtora infestans [20] microorgan isms. Subtilisin like enzymes are secreted by C. carbonum [16], P. infestans [20], Acremonium typhium [21], Magnaporthe poae [22], Trichoderma harzianum [23], and Fusarium oxysporum [24]. Among extracellular proteinas es of phytopathogens, the aspartic proteinases are fairly widespread.…”
mentioning
confidence: 99%
“…It has been reported that pectinases and cutinase secreted by A. flavus during cotton boll and corn infection are related to Aspergillus virulence (Brown et al 1992;Guo et al 1996, Mellon et al 2007. Proteases are other enzymes identified in a number of plant pathogenic fungi and may play a critical role in successful host colonisation (Di Pietro et al 2001;Pekkarinen and Jones 2002;Bindschedler et al 2003). Physiological studies have suggested that proteases could have a direct effect on the proteins of a plant's plasma membrane or cell wall (Movahedi and Heale 1990;Carlile et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The unique protein degradation/assimilation pathway active in the canker pathogen M. populorum allows it to harvest nitrogen from wood, giving it access to a niche in a woody environment. Plant pathogen genomes are generally enriched in secreted trypsin and subtilisin-like peptidases (MEROPS subfamilies S01 and S08) that play a role in pathogenicity and direct degradation of plant cell-wall components, such as hydroxyprolinerich glycoproteins (42,43). An underrepresentation of these subfamilies in M. populorum and M. populicola is balanced by an increase in tripeptidyl-peptidases (S53) and amino-peptidases (M28) (SI Appendix, Tables S5 and S6 and Peptidases).…”
Section: Gene Content and Expression In M Populorum And M Populicolamentioning
confidence: 99%